Strategi Pengembangan Program Studi Manajemen Zakat dan Wakaf di Fakultas Ekonomi dan Bisnis Islam - Sulistia, Yulva; Lubis, Delima Sari; Napitupulu, Rodame Monitorir (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2022)
There has been a decrease in the number of students of the Zakat and Waqf Management study program from year to year, so a study was carried out which aims to find out how the Faculty of Islamic Economics and Business implements strategies to develop it. This type of research is a qualitative research, with the research subjects being students and the Head of the Zakat and Waqf Management Study Program as well as the Dean and Deputy Dean of the Faculty of Economics and Islamic Business. Samples were taken by purposive sampling technique. Data were collected using collection techniques taken from interviews, observations, documentation, and literature studies. The data analysis technique used in this study is the IFAS matrix, EFAS matrix, and SWOT matrix. The score obtained from the IFAS matrix has a total of 3.06, while the total score obtained from the EFAS matrix is 2.68. When viewed from the quadrant, the SWOT matrix shows the position in quadrant I with an aggressive strategy. The strategy that must be carried out is the S-O strategy, the results show that program studies provide a good brand image, provide knowledge and abilities to students, and establish cooperative relationships with related institutions and institutions that are able to provide scholarships for students. Keywords: SWOT Analysis, Zakat and Waqf Management, Strategy